17. PREVELANCE OF MYOPIA AND RELATED FACTOR TO MYOPIA AMONG HIGH SCHOOL STUDENTS (Vietnam Journal of Community Medicine, 2025)
Background: Myopia is a common leading cause which incease the potential risk of refractive error among high school student or eye diseases that threaten global vision, including glaucoma, cataracts, and retinal detachment.Objectives: To determine the prevalence of myopia and relate factors to myopia among high school students at Tuy An District, Phu Yen Province in 2024.Methos: A cross-sectional survey was conducted among 579 students in high schools, Tuy An District, Phu Yen Province from March 27th, 2024 to May 1st, 2024. Subjects were surveyed using a prepared questionnaire and Myopia results were retrieved from their routine health check-up records.Results: The prevalence of myopia in students was 21,6%. The results of the study indicated that students at higher risk of developing myopia were typically femalw, had a family history of myopia, spent more time studying with higher frequency, maintained poor sitting posture, and had a high level of screen usage.  Conclusions: The high prevalance of myopia aming high school students calls for measures to encourage physical activitives and sun exposure, while also limiting the time spent on visually focused activities (studying) and the use of electronic devices with screens.
Keywords: myopia; refrective error; high school students; Phu Yen